2022
DOI: 10.1051/0004-6361/202243894
|View full text |Cite
|
Sign up to set email alerts
|

Prussic

Abstract: Dusty star-forming galaxies (DSFGs) at redshift z ≥ 1 are among the most vigorously star-forming galaxies in the Universe. However, their dense (≥ 10 5 cm −3 ) gas phase -typically traced by HCN(1-0) -remains almost entirely unexplored: only two DSFGs have been detected in HCN(1-0) to date. We present results of a JVLA survey of the J=1-0 transition of HCN, HCO + , and HNC(1-0) in six strongly lensed DSFGs at z = 2.5 − 3.3, effectively doubling the number of DSFGs with deep observations of these lines. We dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 136 publications
0
6
0
Order By: Relevance
“…Similarly, low-redshift LIRGs also show small IR sizes 1-3 kpc (Lutz et al 2016;Bellocchi et al 2022); however, these are commonly confined to merger nuclei, whereas high-z targets can show kinematic evidence for disks with high SFR surface densities (Hodge et al 2016;Calistro Rivera et al 2018;Pantoni et al 2021;Xiao et al 2022). The ISM conditions found within such high-z, dusty star-forming disks seem to resemble those within the cores of local LIRGs (Spilker et al 2016;McKinney et al 2020McKinney et al , 2021aRybak et al 2022).…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, low-redshift LIRGs also show small IR sizes 1-3 kpc (Lutz et al 2016;Bellocchi et al 2022); however, these are commonly confined to merger nuclei, whereas high-z targets can show kinematic evidence for disks with high SFR surface densities (Hodge et al 2016;Calistro Rivera et al 2018;Pantoni et al 2021;Xiao et al 2022). The ISM conditions found within such high-z, dusty star-forming disks seem to resemble those within the cores of local LIRGs (Spilker et al 2016;McKinney et al 2020McKinney et al , 2021aRybak et al 2022).…”
Section: Introductionmentioning
confidence: 97%
“…One possibility is that at high redshift the star formation rate still scales linearly with IR luminosity, but the dense gas fraction is enhanced, driven by some combination of gravitational instabilities from mergers and gas accretion, and extreme stellar feedback from supernovae or radiation pressure (Bournaud et al 2010). However, recent work (Rybak et al 2022) indicates that the dense gas fraction is suppressed rather than enhanced. Another possibility is that the efficiency with which dense gas forms stars depends on the local conditions of the galaxy (Usero et al 2015;Bigiel et al 2016).…”
Section: Dense Gas Tracersmentioning
confidence: 97%
“…Though some excited rotational ground levels are also shown in Figure 7, it is difficult to compare because of the different excitation requirements for 12 CO and the dense gas tracers shown. Recent work (Rybak et al 2022) has found that (U)LIRGs at high redshift have a lower HCN/ CO than the local universe for the J up = 1 transition. Though our results seem to also show lower HCN/CO ratios at high redshift, the SLED of HCN is a subject of ongoing study in the local universe (e.g., Saito et al 2018) and has not been explored at high redshift.…”
Section: Dense Gas Tracersmentioning
confidence: 99%
“…HCN is incidentally detected in the brightest high-redshift galaxies (Riechers et al 2006a(Riechers et al , 2010Oteo et al 2017;Cañameras et al 2021). In contrast, Rybak et al (2022) reported one detection of HCN (1-0) emission line as a result of a deep survey with Karl G. Jansky Very Large Array (VLA) towards six strongly lensed DSFGs. They suggest that in fact most DSFGs have low-dense gas fraction.…”
Section: Linementioning
confidence: 99%
“…We obtain the HCN/CO line luminosity ratio of 𝐿 ′ HCN /𝐿 ′ CO = 0.022 ± 0.008 and an upper limit on the HCO + /CO line luminosity ratio of 𝐿 ′ HCO + /𝐿 ′ CO < 0.024 based on our stacked spectrum. The deep VLA survey from Rybak et al (2022) reports an upper limit in line luminosity ratio of 𝐿 ′ HCN /𝐿 ′ CO < 0.045 and 𝐿 ′ HCO + /𝐿 ′ CO < 0.043, using solely the ground transitions. Since our results use a stack across multiple higher-order transitions, a direct comparison between these results is more difficult, however our results also suggest a dearth of dense gas in the BEARS sample.…”
Section: Linementioning
confidence: 99%